Bullous Grover’s Disease in a Chinese Tibetan Adolescent: A Case Report - Wang Q; Luo N; Lei M; Chen X; Li C; Hao P (Dove Medical Press, 2022)
Qiuyue Wang,1,2,* Nana Luo,1,2,* Min Lei,1,2 Xian Chen,3 Chunxiao Li,2 Pingsheng Hao2 1School of Clinical Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China; 2Department of Dermatology, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China; 3Department of Pathology, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Chunxiao Li; Pingsheng Hao, Department of Dermatology, Hospital of Chengdu University of Traditional Chinese Medicine, No. 39 Shi-er-qiao Road, Chengdu 610075, Sichuan, People's Republic of China, Tel +86-18981937829 ; +86-13881965024, Fax +86-028-87732407, Email chunxiaolee@126.com; hpswl@126.comAbstract: Grover's disease (GD), also known as Transient acantholytic dermatosis, has no typical clinical rash features. It usually occurs in elderly white men but very rarely in China. This is a disease of acantholysis and dyskeratosis, which is usually considered to be spontaneous remission. The skin lesions of the disease are diverse, and the main symptom is severe itching. We have reported a case of GD in a 14-year-old Chinese Tibetan male whose clinical manifestations were pruritic red papule, generalized red papules, papulo vesicles and blisters ranging from millet rice to soybean size. Skin lesions change rapidly and variously. In order to confirm the diagnosis, we have done skin biopsies, immunofluorescence, dermoscopy, microscopy and other examinations. Pathological skin biopsy showed acantholysis. Intraepidermal blisters and the presence of blisters on the basal cells as well as under the stratum corneum can be observed on the same pathological section. Type IV collagen immunohistochemistry showed blisters in the epidermis. The diagnosis of GD depended on the exclusion of other diseases. After we performed whole exon sequencing (WES) on DNA from the patient's blood, pathogenic gene mutations were not found. Pustular psoriasis, Subcorneal pustular dermatosis, Herpesvirus infections, Dermatitis herpetiformis, Pemphigus vulgaris, Norwegian scabies, Darier's disease, and Hailey-Hailey disease were all excluded. We successfully treated adolescent GD with minocycline combined with methotrexate. The patient was followed up for 19 months without recurrence.Keywords: Grover's disease, Chinese, minocycline, methotrexate, adolescent, case report